2009
DOI: 10.1242/jeb.029181
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase and acid–base regulation in fish

Abstract: SummaryCarbonic anhydrase (CA) is the zinc metalloenzyme that catalyses the reversible reactions of CO 2 with water. CA plays a crucial role in systemic acid-base regulation in fish by providing acid-base equivalents for exchange with the environment. Unlike airbreathing vertebrates, which frequently utilize alterations of breathing (respiratory compensation) to regulate acid-base status, acid-base balance in fish relies almost entirely upon the direct exchange of acid-base equivalents with the environment (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
133
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(135 citation statements)
references
References 176 publications
(313 reference statements)
1
133
1
Order By: Relevance
“…Although our understanding of the physiological significance of CA in acid-base/ionoregulation in fish is far from complete, putative roles of CA have been described in several species including zebrafish (for review, see Gilmour, 2012;Gilmour and Perry, 2009). Boisen et al (Boisen et al, 2003) reported that inhibition of CA with ethoxzolamide reduced Na + uptake in adult zebrafish acclimated to hard water, whereas it increased Na + uptake in fish acclimated to soft water.…”
Section: Carbonic Anhydrasementioning
confidence: 99%
See 1 more Smart Citation
“…Although our understanding of the physiological significance of CA in acid-base/ionoregulation in fish is far from complete, putative roles of CA have been described in several species including zebrafish (for review, see Gilmour, 2012;Gilmour and Perry, 2009). Boisen et al (Boisen et al, 2003) reported that inhibition of CA with ethoxzolamide reduced Na + uptake in adult zebrafish acclimated to hard water, whereas it increased Na + uptake in fish acclimated to soft water.…”
Section: Carbonic Anhydrasementioning
confidence: 99%
“…The mechanisms of ionic and acid-base regulation in fish have been summarized in previous reviews (Claiborne et al, 2002;Evans et al, 2005;Gilmour and Perry, 2009;Goss et al, 1992;Haswell et al, 1980;Hwang, 2009;Marshall and Grosell, 2006;McDonald, 1983a;Perry, 1997;Perry and Gilmour, 2006;Wood, 1989). In this review we provide an overview of the general effects of acid exposure on FW fish, with particular emphasis on recent developments linking environmental acidification and ionic regulation in the acid-tolerant zebrafish.…”
mentioning
confidence: 98%
“…CA has been reported in the swim bladder of bowfin (Gervais and Tufts, 1998) and in fish muscle (for review, see Henry and Swenson, 2000). CAs are important in acid-base regulation in many sites including muscle, gills and kidney (Geers and Gros, 2000;Gilmour and Perry, 2009).Teleost fish RBCs have sodium/proton exchange (NHE) isoforms and a Band III anion exchange (AE) protein that take up sodium and chloride and excrete protons and bicarbonate, respectively ( Fig. 3) and are involved in volume regulation (Heming et al, 1986;Claiborne et al, 1999;Cossins and Gibson, 1997;Rummer and Brauner, 2011;Rummer et al, 2010;Weaver et al, 1999).…”
mentioning
confidence: 99%
“…We also found an up-regulation of genes related to carbonic anhydrase activity. This enzyme has been implicated in ion regulation, carbon dioxide (CO 2 ) excretion, and acid base balance in the gills of euryhaline fish (Gilmour and Perry 2009;Gilmour 2012). Indeed, in all comparisons involving wild A. grahami, several isoforms of carbonic anhydrase were found, emphasizing the importance of this enzyme in the metabolism of this species under its native challenging environmental conditions in the wild (Table S5).…”
Section: Gene Expression Changes In a Grahamimentioning
confidence: 97%